Pengaruh Safety Introduction dan Kompetensi Awak Kapal terhadap Keselamatan Pelayaran dan Dampaknya terhadap Kinerja Operasional Kapal di Kawasan Pelabuhan Tanjung Perak Surabaya - Angga Wahyu Saputra; Freddy J. Rumambi; Nofrisel Nofrisel (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to analyze the effect of safety introduction and crew competence on ship operational performance and the role of passenger safety as a mediating variable on ships operating at Tanjung Perak Port. This study uses a quantitative approach with the SEM-PLS analysis model. This study involved 150 respondents of crew members operating at Tanjung Perak Port. Data collection in this study used questionnaires and field observations. The results of the study indicate that safety introduction has been proven to have an effect on Shipping Safety and operational performance. Thus, it can be implied to the management of ships operating at Tanjung Perak Port to make policies to improve safety introduction in their operations. The results of the study indicate that crew competence affects Shipping Safety and the company's operational performance. Through these results, the policy of ships operating at Tanjung Perak Port should use policies to improve crew competence through training, certification and so on which can ultimately guarantee Shipping Safety and improve performance for the company. The results of the study indicate that Shipping Safety can perfectly mediate the influence between variables in this study. Therefore, the policy implications that can be implemented by ships operating at Tanjung Perak Port are to always pay attention and increase vigilance to ensure shipping safety and ensure shipping safety, one of which is through efforts in safety introduction procedures and increasing the competence of the ship's crew, which can ultimately improve the company's performance.